2008
DOI: 10.1074/jbc.m706851200
|View full text |Cite
|
Sign up to set email alerts
|

N Terminus of Calpain 1 Is a Mitochondrial Targeting Sequence

Abstract: The ubiquitous m-and -calpains are thought to be localized in the cytosolic compartment, as is their endogenous inhibitor calpastatin. Previously, -calpain was found to be enriched in mitochondrial fractions isolated from rat cerebral cortex and SH-SY5Y neuroblastoma cells, but the submitochondrial localization of -calpain was not determined. In the present study, submitochondrial fractionation and digitonin permeabilization studies indicated that both calpain 1 and calpain small subunit 1, which together form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 70 publications
(68 reference statements)
1
51
0
Order By: Relevance
“…Similarly, we have recently observed that stimulation of mitochondrial ROS production promotes Ca 2 þ -mediated AIF processing (data not shown). Hence, the results obtained in earlier studies, 23,33 along with our current observations, suggest a scenario in which the processing of AIF might be regulated by a three-step mechanism. First, a prolonged increase in Ca 2 þ level activates mitochondrial calpain in the IMS.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Similarly, we have recently observed that stimulation of mitochondrial ROS production promotes Ca 2 þ -mediated AIF processing (data not shown). Hence, the results obtained in earlier studies, 23,33 along with our current observations, suggest a scenario in which the processing of AIF might be regulated by a three-step mechanism. First, a prolonged increase in Ca 2 þ level activates mitochondrial calpain in the IMS.…”
Section: Discussionsupporting
confidence: 49%
“…It has recently been shown that calpain I contains a mitochondrial localization signal and that the small subunit of calpain I can be coimported into the IMS together with the calpain I large subunit. 23 In addition, the mitochondrial localization of calpain I was also demonstrated by live imaging of cells transfected with a GFP construct containing the N terminal of calpain I. The authors suggested that the mitochondrial outer membrane represents a barrier separating calpain I from its endogenous inhibitor calpastatin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations